Endoscopic ultrasonography‐guided tumor ablation. Issue 4 (16th March 2017) - Lakhtakia, Sundeep; Seo, Dong‐Wan
Abstract : Real‐time guidance of needle advancement has transformed endoscopic ultrasound (EUS) from a diagnostic to an interventional procedure. EUS‐guided fine‐needle puncture has application in various interventional procedures (drainage of pseudocyst, biliary intervention, and injection of drugs). Celiac plexus or ganglion neurolysis for pain control is the major current EUS‐guided fine‐needle injection procedure. Feasibility and safety to accurately position needle devices and/or inject under real‐time EUS imaging with precise delivery of interventional agent have expanded the use of EUS to ablate tumors. These include radiofrequency ablation, or delivery of fiducial markers, potential antitumor agents, or radioactive seeds, in the cancer mass. Minimally invasive EUS‐guided antitumor therapy is primarily used for pancreatic cancer because of better anatomic access ( vs other imaging modality) and the dismal prognosis (despite improvements in surgery and chemoradiation). Also, the response to parenteral chemotherapy in pancreatic cancer is poor because of suboptimal drug delivery resulting from hypovascularity and abundant desmoplasia. Other targets for EUS‐guided tumor ablation are pancreatic neuroendocrine tumor and pancreatic cyst lesion, which are less aggressive and curable by resection. However, patients non‐eligible for surgery may benefit from local EUS‐guided ablation.